2008
DOI: 10.1016/j.neuroscience.2008.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of the invertebrate FMRFamide–gated sodium channel as a mechanism to selectively activate mammalian neurons

Abstract: Considerable effort has been directed toward the development of methods to selectively activate specific subtypes of neurons. Focus has been placed on the heterologous expression of proteins that are capable of exciting neurons in which they are expressed. Here we describe the heterologous expression of the invertebrate FMRFamide-gated sodium channel from Helix aspersa (HaFaNaC) in hippocampal slice cultures. HaFaNaC was co-expressed with a fluorescent protein (GFP, dsRed or tdTomato) in CA3 pyramidal neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 94 publications
2
13
0
Order By: Relevance
“…These data are informative as they provide an insight regarding when other aromatic amino acids can replace phenylalanine and the neuropeptide can still be considered a FLP in terms of FLP-like activity. HaFaNaC has been expressed in CA3 pyramidal neurones from rat hippocampal slice cultures (Schanuel et al 2008). FMRFa depolarizes and excites these neurones inducing bursts of activity, and this effect is blocked by amiloride.…”
Section: Molluscsmentioning
confidence: 99%
“…These data are informative as they provide an insight regarding when other aromatic amino acids can replace phenylalanine and the neuropeptide can still be considered a FLP in terms of FLP-like activity. HaFaNaC has been expressed in CA3 pyramidal neurones from rat hippocampal slice cultures (Schanuel et al 2008). FMRFa depolarizes and excites these neurones inducing bursts of activity, and this effect is blocked by amiloride.…”
Section: Molluscsmentioning
confidence: 99%
“…Slice cultures were prepared using the method of Stoppini et al (Stoppini et al, 1991), as previously reported by (Schanuel et al, 2008). All animal use protocols are in strict accordance with the National Institute of Health guidelines and are approved by the International Animal Care and Use Committee of Virginia Commonwealth University.…”
Section: Methodsmentioning
confidence: 99%
“…In another example, it has been shown that heterologous expression of FaNaC in mammalian hippocampal neurons provides a means to depolarize the neurons and induce bursts of action potentials upon focal application of FMRFa (Schanuel et al, 2008). FaNaC has a somato-dendritic localization and is absent from axons (Schanuel et al, 2008).…”
Section: Measuring Neuropeptide Levelsmentioning
confidence: 99%
“…In another example, it has been shown that heterologous expression of FaNaC in mammalian hippocampal neurons provides a means to depolarize the neurons and induce bursts of action potentials upon focal application of FMRFa (Schanuel et al, 2008). FaNaC has a somato-dendritic localization and is absent from axons (Schanuel et al, 2008). As FMRFa is not present in the mammalian nervous system, and endogenous RFamides apparently do not activate FaNaC (Schanuel et al, 2008), it is in principle possible to activate specific subsets of neurons selectively in intact nervous tissue.…”
Section: Measuring Neuropeptide Levelsmentioning
confidence: 99%
See 1 more Smart Citation